Comparison of different methods for normal stress calculation during pipe jacking/microtunneling. Issue 4 (7th August 2016) - Khondoker, Md. Tareq Hossain; Yi, Yaolin; Bayat, Alireza
Abstract : Vertical earth load on pipes is an important factor during pipe jacking/microtunneling as it largely affects the jacking force. Although several methods can determine the normal load, the difference among them in calculating vertical normal stress is quite large. Hence, this paper provides an extensive analysis of nine different models/standards and their variations based on experimental data as well as a parametric study. The results show that some models predicted normal stress values close to the measured value, while others give much higher or lower values than the measurement. This discrepancy is due to the variation of assumptions of different methods. To identify the influence of parameters on normal stress, a parametric study is also conducted to reveal the effect of different parameters on arching factor as well as normal earth stress.